Microscopic Analysis of Hybrid Synthetic/Vegetable Fiber-Reinforced Epoxy Composites - Monticeli, Francisco M. [UNESP]; Neves, Roberta M.; Almeida, José Humberto S.; Ornaghi, Heitor Luiz (My University, 2022)
Hybridization of synthetic with natural fibers has been increasingly studied over the last decades given the potential to partially replace glass fibers with natural ones aiming at meeting both design requirements and environmental concerns. Despite some drawbacks about natural fibers, such as high moisture absorption and low mechanical properties, the combination with synthetic fibers is a suitable route to overcome these drawbacks. Usually, hybrid fiber-reinforced composites need to meet mechanical constraints, and consequently the microstructure of the composite must be taken care of to generate structures with proper mechanical performance. This chapter presents a systematic review on hybrid synthetic/vegetable composites reinforced epoxy composites focusing on research papers published from 2016 to 2020. A total of 531 papers were initially found, but after the exclusion criteria following the PRISMA protocol, 32 articles remained and were included in this review. The presented results focus on the type of microscopy method and analysis of the composites. In brief, this study aims to help to identify the main gaps in the literature related to the proposed topic.
Keywords: Hybrid composites; Microscopy; Systematic review; Void